Metastable Nanoporous Palladium Evolving from Palladium Nanocrystals. Issue 10 (1st August 2021) - Teraji, Satoshi; Samitsu, Sadaki; Tran‐Cong‐Miyata, Qui; Norisuye, Tomohisa; Nakanishi, Hideyuki
Abstract: Nanoporous metals can be used in many technological applications, and continuous interest has been focused on their preparation. In this study, we describe a different type of preparation method, in which nanoporous palladium (Pd) is prepared from Pd nanocrystals by the elimination of stabilizers. The resulting nanoporous Pd has a bimodal pore structure with an extensive surface area, and its surfaces are electrochemically accessible and exhibit higher catalytic activity toward ethanol electrooxidation than that of the commercial Pd black catalyst. An interesting feature is that the atomic surface structure can be sensitively altered by the preparation temperature and solvent, thereby increasing the catalytic activity of nanoporous Pd. The proposed method is simple and available for mass production and is expected to be a new alternative for producing electrochemically active nanoporous Pd. Abstract : This study reports that Pd nanocrystals structurally evolve into nanoporous Pd with a bimodal pore structure. The resulting nanoporous Pd forms a metastable structure and promotes ethanol electrooxidation, and its catalytic activity is improved by modifying preparation temperature and solvent. The proposed approach is simple, and extending it may open a new avenue for the preparation of nanoporous Pd.